油酸直接马来酸化制备C22 -三元羧酸Preparation of C22-tricarboxylic acid by Maleinisation of oleic acid - 陈治家，赵杰，张铭远，邓林江，钮腾飞 CHEN Zhijia，ZHAO Jie，ZHANG Mingyuan，DENG Linjiang，NIU Tengfei (Zhongguo youzhi, 2023)
为解决C22-三元羧酸合成过程中均相催化剂残留、原料价格较高等问题，以油酸为原料，在路易斯酸催化下与马来酸酐进行Alder-ene加成反应，水解后得到C22-三元羧酸。对C22-三元羧酸的合成条件进行优化并对产物进行了鉴定；制备C22-三元酸钠表面活性剂并研究其表面性能。结果表明：C22-三元羧酸合成的最佳条件为以FePO4为催化剂、催化剂用量3%（以油酸物质的量计）、马来酸酐与油酸物质的量比3∶ 1、反应温度180 ℃、反应时间10 h，在此条件下C22-三元羧酸产率达到78%，油酸转化率为77.4%；通过质谱及核磁共振表征证明得到了较纯的C22-三元羧酸；催化剂经过5次回收利用并未出现明显的活性降低；以C22-三元羧酸为原料制备的C22-三元酸钠表面活性剂的临界胶束浓度为3.61×10-3 mol/L，在临界胶束浓度下的表面张力为28.39 mN/m。综上，油酸在FePO4催化下直接马来酸化制备C22-三元羧酸，工艺绿色，原料成本较低，并可作为表面活性剂制备的良好原料。 To solve the problems of homogeneous catalyst residue and high raw material price in the synthesis of C22-tricarboxylic acid, using oleic acid as the raw material, Lewis acid as catalyst, the Alder-ene addition reaction of oleic acid and maleic anhydride was realized, and C22-tricarboxylic acid was obtained after hydrolysis. The synthesis conditions of C22-tricarboxylic acid were optimized and the product was identified, and its product was neutralized to prepare C22-tribasic acid sodium surfactant and its surface properties were studied. The results showed that the optimal conditions for C22-tricarboxylic acid synthesis were obtained as follows: with Lewis acid FePO4 as catalyst, dosage of catalyst 3% (calculated by the mole of oleic acid ), molar ratio of maleic anhydride to oleic acid 3∶ 1, reaction temperature 180 ℃, and reaction time 10 h. Under the optimal conditions, the yield of C22-tricarboxylic acid could reach 78% and oleic acid conversion rate was 77.4%. It was proved that C22-tricarboxylic acid was obtained through mass spectrometry and nuclear magnetic resonance characterization. There was no obvious decrease in activity of catalyst after 5 times of recycling. The critical micelle concentration of C22-tribasic acid sodium surfactant prepared by C22-tricarboxylic acid was 3.61×10-3 mol/L, and the surface tension(γ) reached 28.39 mN/m. In conclusion, the preparation process of C22-tricarboxylic acid by the Alder-ene addition reaction of oleic acid and maleic anhydride with FePO4 as catalyst is green and the cost of materials is low， and the C22-tricarboxylic acid prepared can used as good material for surfactant preparation.